PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN INSENTIF TERHADAPKINERJA PADA KARYAWAN ASN UPTD PUSKESMAS CERMEE BONDOWOSO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Hurriyah, Hilyatul; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2024)
The position and function of the State Civil Apparatus as part of the State apparatus which is responsible as a public servant must provide equitable services to the community, with the principles of loyalty and compliance with Pancasila and the 1945 Constitution. The aim of this research is to analyze and test the influence of Work Discipline , Work Environment and Incentives on the Performance of ASN Employees at the Cermee Bondowoso Health Center UPTD with Job Satisfaction as an intervening variable. This research is explanatory research. The population in this study were ASN UPTD employees of the Cermee Bondowoso Community Health Center. The sampling technique uses a saturated sample technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Work Discipline has a significant positive effect on Job Satisfaction, Work Environment has a positive but not significant effect on Job Satisfaction, Incentives have a significant positive effect on Job Satisfaction, Work Discipline has a negative but not significant effect on Performance , Work Environment has a significant negative effect on Performance, Incentives have a significant positive effect on Performance. The results of the indirect influence hypothesis test show that the variables that work discipline has a significant positive effect on performance through job satisfaction, the work environment has a negative but not significant effect on performance through job satisfaction, and incentives have a significant positive effect on performance through job satisfaction.